Etiology of Post-Covid Fungal Infections among Various Age Groups at Teritiary Care Hospital (Indian Journal of Public Health Research & Development, 2022)
Background: In patients with comorbid illnesses, COVID 19 disease is a severe acute respiratory syndrome that is linked to a variety of opportunistic bacterial and fungal infections. Finding the cause of fungal infections among post-covid patients in tertiary care hospitals is the aim of the study.Objectives: To study the etiology of post-covid fungal infections among various age groupsMethods: Out of 578 samples (pus/tissue/biopsy) collected from patients attending Koti ENT hospital with complaints of pain in eye, cheek swelling, headache. All samples were subjected to direct KOH mount and inoculated on SDA, incubated for 1 week at 25°C.Result: Out of 578 samples 214 are KOH positive and 291 are culture positive with fungi isolated – Mucor species, Aspergillus species and Candida species.Conclusion: As post covid fungal infections are rapidly progressive and devascularised disease, timely diagnosis helps in effective management and treatment of patients
Keywords: : Mucormycosis, COVID-19, diabetic, KOH, SDA, fungi